2020
DOI: 10.1016/j.celrep.2020.107960
|View full text |Cite
|
Sign up to set email alerts
|

A Trio of Active Zone Proteins Comprised of RIM-BPs, RIMs, and Munc13s Governs Neurotransmitter Release

Abstract: Highlights d RBP and RIM are needed for sufficient Ca 2+ influx d RBP2 primes synaptic vesicles via Munc13-1 at small central synapses d RBP2 controls short-term plasticity by vesicle priming or Ca 2+ -channel recruitment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…For IHC AZs, this has been suggested to reflect a role of RIM-BP2 in registering new-coming SVs in nanoscale proximity of Ca 2+ channels (Krinner et al, 2017). Recently, a role of RIM-BP in SV priming via interaction with Munc13-1 has been suggested (Brockmann et al, 2020). As priming of SVs in IHCs seems to operate without Munc13 and CAPS priming proteins (Vogl et al, 2015), other protein interactions such as the one with CAST/ELKS (Petzoldt et al, 2020) remain to be studied for a potential involvement in SV replenishment.…”
Section: Introductionmentioning
confidence: 99%
“…For IHC AZs, this has been suggested to reflect a role of RIM-BP2 in registering new-coming SVs in nanoscale proximity of Ca 2+ channels (Krinner et al, 2017). Recently, a role of RIM-BP in SV priming via interaction with Munc13-1 has been suggested (Brockmann et al, 2020). As priming of SVs in IHCs seems to operate without Munc13 and CAPS priming proteins (Vogl et al, 2015), other protein interactions such as the one with CAST/ELKS (Petzoldt et al, 2020) remain to be studied for a potential involvement in SV replenishment.…”
Section: Introductionmentioning
confidence: 99%
“…What might be the consequence of the variable amounts of Munc13-1 in RSs? Munc13-1 is an evolutionally conserved presynaptic protein that is essential for docking and priming vesicles for release (Augustin et al, 1999;Betz et al, 2001;Brockmann et al, 2020;Imig et al, 2014;Jahn and Fasshauer, 2012;Ma et al, 2011;Varoqueaux et al, 2002) therefore it can be hypothesized that the amount of this molecule might have an effect on the docking site occupancy or the priming state of the vesicles. MPFA only allows the determination of Pv, a probability that depends on the probability of the RS being occupied (Pocc) and on the probability of a docked vesicle being released (Psucc; Neher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is just as unknown whether the normally and superprimed vesicles need different amounts of Munc13-1 or not. It is noteworthy that the priming efficacy of Munc13-1 depends on its interaction with RIM and RIM binding protein (Brockmann et al, 2020) AZs. Maschi and Klyachko (2020) demonstrated that the Pv of centrally located RSs is higher and participate more frequently in multivesicular release (MVR) than those that are located at the periphery of the AZs.…”
Section: Discussionmentioning
confidence: 99%
“…This might relate to partial compensation by other candidate linkers of CaV and SV release sites such as long RIM isoforms (Acuna et al, 2016). Recently, two alternative actions of RIM-BPs were indicated based on molecular perturbations studies in hippocampal neurons: i) binding to CaV enabling their tight coupling to SVs or ii) promoting SV priming by interaction with Munc13-1 (Brockmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%